Civil Servants Management Reform in West Java Province: A Case Study - Edy Sutrisno (Jurnal Good Governance, 2020)
The West Java Province has for the past several years been awarded as the best performing national provincial government. One of its successes was in implementing reforms in the management of civil servants. This study uses a qualitative approach that is carried out by the case study method. The implementation of the reform of the management of Civil Servants in the West Java Province is already underway but there are still problems that must be resolved immediately so that the implementation of reforms runs more effectively. It is hoped that this research can provide suggestions for improving the practice of reforming the management of civil servants in the Government of West Java Province, Indonesia.Key Word: cicil servants reform, administratif reform, cicil servants management.